Digital Transformation Strategy in Advertising: A Study Bibliometric Analysis - Sukmono, Filosa Gita; Lestari, Nastiti Dyah; A. Rahman, Suria Hani; Ahmad, Murtada Busair (Komunikator, 2024)
This study analyzes digital transformation in advertising strategies. A search using the keywords “Digital Transformation” and “Advertising” in the Scopus database yielded 114 documents. Using the PRISMA method, the researchers applied inclusion criteria, selecting articles, conference papers, book chapters, conference reviews, books, and reviews available in English, Spanish, Portuguese, German, and Russian. This bibliometric analysis identified key themes, such as “Digital Transformation,” “Advertising,” and “Artificial Intelligence,” with the United States and Germany as the most influential countries. Eight thematic clusters were identified, such as digital transformation based on data and technology, digital business management, digital marketing strategy, data-driven marketing automation, technology, and workforce management, digital innovation in sustainable marketing, technology integration and professional skills development, communication in digital marketing, and the impact of COVID-19 on marketing models. This pioneering bibliometric study provides essential insights for academics and professionals aiming to understand current advancements in digital transformation within advertising. Companies are encouraged to integrate artificial intelligence into digital campaigns to improve personalization and effectiveness in advertising strategies.